2009
DOI: 10.1093/rheumatology/kep262
|View full text |Cite
|
Sign up to set email alerts
|

Identification of phenotypic discriminating markers for intervertebral disc cells and articular chondrocytes

Abstract: Our study shows that NP and AF cells exhibit a clearly distinguishable phenotype from that of AC. Type V collagen, MGP and HtrA1 could greatly help to discriminate among NP, AF and AC cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 25 publications
3
65
0
1
Order By: Relevance
“…Spontaneous disc regression is currently believed to be a consequence of macrophage activity. [35,36] type XI [37] all over, mostly NP regulates fibril diameter (smaller if this collagen is more abundant) influencing mechanical properties [35,38] beaded-filament forming collagens type VI all over, mostly NP helps cell fixation to the matrix and facilitates collagen bundles' sliding and lubrication [39,40] FACIT collagens type IX NP maintains matrix integrity [41,42] type XII AF might regulate fibrillogenesis [29,43] [66,[74][75][76]. However, when an imbalance occurs, degradation products might trigger inflammation.…”
Section: The Origin Of Inflammation In Intervertebral Discmentioning
confidence: 99%
“…Spontaneous disc regression is currently believed to be a consequence of macrophage activity. [35,36] type XI [37] all over, mostly NP regulates fibril diameter (smaller if this collagen is more abundant) influencing mechanical properties [35,38] beaded-filament forming collagens type VI all over, mostly NP helps cell fixation to the matrix and facilitates collagen bundles' sliding and lubrication [39,40] FACIT collagens type IX NP maintains matrix integrity [41,42] type XII AF might regulate fibrillogenesis [29,43] [66,[74][75][76]. However, when an imbalance occurs, degradation products might trigger inflammation.…”
Section: The Origin Of Inflammation In Intervertebral Discmentioning
confidence: 99%
“…Therefore, we also examined phenotype of CD271 -MSCs and used PA-MSCs as a control cell population for the both isolated CD271 cell subsets. Although the phenotype of NP cells is closely associated with that of chondrocytes, still clear differences exist [41]. Similarly to the in vitro differentiation of MSCs into chondrocytes, their differentiation toward an NP-cell phenotype depends on diverse and specific parameters such as an appropriate choice of growth factors, 3D-matrix, intercellular contacts or environmental conditions mimicking the physiological status of IVD such as hypoxia [34].…”
Section: Discussionmentioning
confidence: 99%
“…Although definitive phenotypic markers could not be identified, Clouet et al (2009) reported higher expression of type V collagen in rabbit AF than NP cells or articular chondrocytes. However, there are interspecies differences in gene expression (Pattappa et al, 2012).…”
Section: The Molecular Biology Of Anulus Fibrosus Components and Theimentioning
confidence: 97%
“…Although they are not absolutely definitive, they help us to understand the development and metabolism of NP cells and monitor the phenotype of MSC as they differentiate into an NP-like phenotype (Pattappa et al, 2012). In both healthy and degenerative discs, NP cells express chondrocyte markers such as SOX-9 and collagen type II (Clouet et al, 2009;Sive et al, 2002). In rats, COMP and MGP are more highly expressed in aged (24 months) rats than immature (three months) rats.…”
Section: Cellular Differentiationmentioning
confidence: 99%